2009
DOI: 10.1097/01.ncq.0000347452.36418.78
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Satisfaction and Creation of an Admission, Discharge, and Teaching Nurse Position

Abstract: The goal of this study was to evaluate the effect of a newly developed nurse admission, discharge, and teaching position on nurse satisfaction and the quality of the admission and discharge process. A pretest-posttest design was used to collect data on nurse satisfaction, workload, and medication reconciliation. Study results supported the use of an admission, discharge, and teaching nurse to improve nurse satisfaction and the quality of the admission and discharge process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
0
11
0
3
Order By: Relevance
“…Estudos sugerem a necessidade de um PA padronizado (5,25,36) para maior eficácia e qualidade do cuidado, com o intuito de garantir a continuidade do cuidado domiciliar (12,33) , a fim de proporcionar aos pacientes informações e recursos necessários para melhorar ou manter a saúde, prevenir EAM e evitar reinternações (26,36) . Nesse processo, deve-se dar ênfase ao PA individualizado a partir da admissão do paciente, envolvendo toda equipe de saúde (15,17,36) .…”
Section: Processo De Alta Hospitalarunclassified
See 1 more Smart Citation
“…Estudos sugerem a necessidade de um PA padronizado (5,25,36) para maior eficácia e qualidade do cuidado, com o intuito de garantir a continuidade do cuidado domiciliar (12,33) , a fim de proporcionar aos pacientes informações e recursos necessários para melhorar ou manter a saúde, prevenir EAM e evitar reinternações (26,36) . Nesse processo, deve-se dar ênfase ao PA individualizado a partir da admissão do paciente, envolvendo toda equipe de saúde (15,17,36) .…”
Section: Processo De Alta Hospitalarunclassified
“…Pesquisas baseadas em evidências sobre educação do paciente e PA são limitadas na literatura (17) , apesar de o PA ser uma exigência da Joint Commission aos hospitais, especialmente no que tange à utilização de medicamentos (18) .…”
Section: Introductionunclassified
“…22,23 For instance, a distinct role for nurses in discharge planning with an explicit protocol to support this role may help promote nurses' knowledge and motivation to be involved in discharge planning. 22 Greater compliance may also occur if nurses are involved in the development and implementation of the protocol and then provided with education and regular feedback on monthly audit results.…”
Section: Implications For Practicementioning
confidence: 99%
“…Lane, Jackson, Odom, Cannella, and Hinshaw (), in looking at an admission and discharge nurse team (ADT) state that, “Unfortunately, the effectiveness of these job positions on nurse satisfaction and patient outcomes is unknown because the ­literature on the topic is primarily ­anecdotal or descriptive in nature” (p. 148). Lane et al () found ­difficulty accessing evidence‐based ­articles on utilizing an ADT to facilitate time‐consuming processes such as admissions and discharges. Lane et al's () study findings suggest decreased nurse workload, increased nurse satisfaction with the ADT and supports the use of this position.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Lane et al () found ­difficulty accessing evidence‐based ­articles on utilizing an ADT to facilitate time‐consuming processes such as admissions and discharges. Lane et al's () study findings suggest decreased nurse workload, increased nurse satisfaction with the ADT and supports the use of this position.…”
Section: Review Of the Literaturementioning
confidence: 99%